The Relational Value of Network Experience in Teams: Evidence From the English Premier League. (September 2016) - Grund, Thomas U.
Previous studies indicate the importance of experience for the performance of teams. Theory suggests that working together allows individuals to (a) improve their knowledge about who knows (and can do) what and (b) facilitates learning to combine individual resources efficiently. Yet it remains elusive how experience translates into interaction patterns in teams. Drawing on unique data of career histories of 800 players and 283, 259 passes between these players in 760 English Premier League soccer matches, I propose a new measure for network experience and demonstrate how it relates to network intensity and decentralization in teams. Soccer teams exhibit a higher passing rate when players know each other from before. At the same time, network experience has no effect on the decentralization of team play. Further dyadic analyses confirm these findings. Controlling for selection effects, two players are more likely to pass the ball between each other when they know each other more. Network experience affects the way team members interact and ultimately leads to performance outcomes.